“A King in Every Countrey”: English and French Encounters with Indigenous Leaders in Sixteenth-Century America - Cook, Peter (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
Beginning with Columbus’ 1493 report of kings among the “Indians,” European expeditionaries regularly perceived Indigenous leaders as kings during the first century of colonialism in the Americas. English and French narratives of the sixteenth century, following the models of early Spanish and Portuguese accounts, brought to light the existence of Aboriginal monarchs throughout the Americas, from the Arctic to Brazil and from New England to California. Popular compilations of travel accounts only cemented the trope in the European imagination. The ubiquity of such kings in early English and French colonial writing reveals the conceptual frameworks through which colonizers perceived the New World and the logic of the strategies they devised to conquer it. Toward the end of the sixteenth century, English and French views diverged, with the latter demonstrating a general reluctance to use the term “king” for Native American leaders. By contrast, English sources would continue to employ the vocabulary of kingship for this purpose into the nineteenth century.